RENCANA ANGGARAN BIAYA STRUKTUR PEMBANGUNAN MASJID POLITEKNIK DI TANGERANG MENGGUNAKAN METODE AHSP PUPR 2023 - Fathu Rahman; Ninik Paryati; Rika Sylviana; Anita Mardiyana Agussalim (CV. Denasya Smart Publisher, 2025)
The preparation of the Bill of Quantity (BoQ) or Cost Budget Plan (Rencana Anggaran Biaya/RAB) is one of the crucial stages in the construction project planning process, which must be carried out before the physical implementation of the project begins. The RAB reflects a comprehensive cost estimate required for a project, covering both labor wages and material procurement. This document contains detailed information on the volume of work, unit prices, and total costs for each component necessary for the realization of the project. One of the commonly used approaches for preparing RAB in Indonesia is the Unit Price Analysis Method (Analisa Harga Satuan Pekerjaan/AHSP). This method is considered capable of producing efficient and accountable cost estimates in accordance with applicable national standards. This study aims to identify economical unit price estimations that can serve as a reference for cost estimators in planning construction project budgets. The research adopts a quantitative approach by analyzing data through volume calculations based on technical drawings, followed by the application of the AHSP 2023 method to determine unit prices, and organizing the results into a BoQ format using Microsoft Excel. The findings indicate that the total estimated cost for the structural development of the State College of Accountancy (Politeknik Keuangan Negara STAN) Mosque in Tangerang is IDR 10,935,996,000.00, which includes all components of work ranging from land excavation, foundation work, and structures for floors 1 to 3, to roof construction, as well as the foundation and structure of the mosque tower. The total cost already includes a contractor's profit margin of 10% and taxes (VAT and Income Tax) of 10%. The largest portion of the budget is allocated to the structure of the first floor, accounting for 23% of the total budget. These findings emphasize the importance of accurate planning in the early stages of a project to minimize potential financial risks in subsequent phases.